Facilitating right‐sided axillary artery access for transcatheter aortic valve replacement using the Edwards Sapien 3 and ultra valves: Technical considerations. Issue 7 (21st October 2019) - Rajkumar, Christopher A.; Cook, Christopher; Shalhoub, Joseph; Chukwuemeka, Andrew; Jaffer, Usman; Hadjiloizou, Nearchos; Sen, Sayan; Ruparelia, Neil; Mikhail, Ghada; Malik, Iqbal S.
Abstract: Trans‐Axillary Transcatheter Aortic Valve Replacement (TAVR) has become established as the safest arterial approach when femoral arterial anatomy is unfavorable. Although a left sided axillary approach is generally preferred, patient specific factors may require use of the right axillary artery. In this case series we describe procedural modifications that are required to overcome the challenge of restricted space in the ascending aorta for in situ valve preparation of balloon‐expandable valve systems when a right sided trans‐Axillary approach is taken. These steps permit implantation of both the Edwards LifeSciences Sapien 3 and Ultra prostheses via the right trans‐Axillary approach, allowing patients a greater range of valve options when this arterial route is required for TAVR.